2020
DOI: 10.1063/5.0032774
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effect of serration shape and flexibility on trailing edge noise

Abstract: In this study, we investigated the performance of flexible trailing edge serrations of various shapes for airfoil self-noise reduction through anechoic wind tunnel experiments. A flat plate model was tested at zero angle of attack. The chord-based Reynolds number was between 1.6 × 105 and 4 × 105. The boundary layers were fully tripped near the leading edge. Add-on type trailing edge serrations were cut from flexible polyethylene terephthalate sheets. It is observed that compared with rigid serrations, flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…There is a fair scaling with 𝑆𝑡 𝛿 * 𝑆𝑆 , which supports previous results that showed that the noise reduction maximum depends on 𝑈 [35,36]. Two regions of noise reduction are identified for both serrations in the LRM results (AWB and TUD-A) The second noise reduction peak is similar to the results of P. Zhou et al [37], which were also measured at similar 𝑅𝑒 𝑐 number as the LRM. The HRM measurements (DTU) show two noise reduction regions in the sawtooth case, but only one in the iron case.…”
Section: Noise Reduction Comparison With Different Serrationssupporting
confidence: 88%
See 1 more Smart Citation
“…There is a fair scaling with 𝑆𝑡 𝛿 * 𝑆𝑆 , which supports previous results that showed that the noise reduction maximum depends on 𝑈 [35,36]. Two regions of noise reduction are identified for both serrations in the LRM results (AWB and TUD-A) The second noise reduction peak is similar to the results of P. Zhou et al [37], which were also measured at similar 𝑅𝑒 𝑐 number as the LRM. The HRM measurements (DTU) show two noise reduction regions in the sawtooth case, but only one in the iron case.…”
Section: Noise Reduction Comparison With Different Serrationssupporting
confidence: 88%
“…At this point we cannot rule out that the noise reduction mechanisms behave differently at high Reynolds numbers. [37] found that this second peak was highly dependant on the serration flexibility and the flow alignment. The serration deformation was dependant not only on the stiffness and flow speed but also on the aerodynamic loading, which is directly related to the serration geometry.…”
Section: Noise Reduction Comparison With Different Serrationsmentioning
confidence: 95%
“…2018; Zhou et al. 2020). Second, the Green's function would provide a more intuitive understanding of the effects of serrations by showing the scattering characteristics of simple sound sources, thereby lending insights into the physical mechanism of noise reduction by using serrations, and more importantly informing on new techniques of suppressing TE noise.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Green's function itself is fundamentally important in many important aspects concerning TE noise. First, this would open the possibility of examining the consequences of many assumptions that have been open to heated debate, such as the validity of frozen turbulence that has been called into question in a number of recent studies (Ragni et al 2018;Zhou et al 2020). Second, the Green's function would provide a more intuitive understanding of the effects of serrations by showing the scattering characteristics of simple sound sources, thereby lending insights into the physical mechanism of noise reduction by using serrations, and more importantly informing on new techniques of suppressing TE noise.…”
Section: Introductionmentioning
confidence: 99%
“…An improved understanding of the underlying physics would almost certainly provide a new avenue to elevate the serration technology to the next level. For example, the flexible serrated trailing edge studied by Zhou et al (2020) is found to achieve additional 2 − 3 dB broadband noise reduction at high-frequency. Setting a spanwise periodicity for the trailing edge serrations can also achieve further level of broadband noise reduction (Woodhead et al 2017).…”
Section: Graphic Abstract 1 Introductionmentioning
confidence: 99%